Episodic Earthquake Swarms in the Mineral Mountains, Utah Driven by the Roosevelt Hydrothermal System. Issue 6 (3rd June 2021) - Mesimeri, Maria; Pankow, Kristine L.; Baker, Ben; Hale, J. Mark
Abstract: Over 1, 000 earthquakes (−2.0 <  M  < 2.0), identified using a matched‐filter method, occurred in the Mineral Mountains, Utah between 2016 and 2019. The enhanced catalog is complete down to M −0.9 and contains roughly 15 times more events than originally cataloged. Earthquake relocation of ∼800 earthquakes shows that activity is concentrated in a <2 km long E‐W striking narrow zone, ∼4 km east of the Roosevelt hydrothermal system. Two fault orientations, both N‐S and E‐W parallel to the Opal Mound and Mag Lee faults, respectively, are observed after computing composite focal mechanisms of highly similar earthquakes. Looking solely at the temporal distribution of the seismicity, we identify 15 periods of swarm‐like activity, with two major clusters occurring in December 2016, recorded by three stations, and in October 2019 recorded by eight stations. The October 2019 swarm, the best recorded sequence in the area, provides evidence for the underlying triggering mechanism. We show that a complex mechanism of fluid diffusion and aseismic slip is responsible for the swarm evolution with migration velocities reaching 10 km/day. We hypothesize that these episodic swarms in the Mineral Mountains are primarily driven by migrating fluids that originate within the Roosevelt hydrothermal system. Plain Language Summary: We use 75 earthquakes and identify over 1, 000 earthquakes (−2.0 < M < 2.0) that occurred in the Mineral Mountains, Utah between 2016 to 2019. Seismic activity is spatially concentrated in a <2 km long E‐W striking narrow zone, ∼4 km east of the Roosevelt hydrothermal system. Looking at the temporal distribution of the seismicity, we identify 15 periods of elevated activity with two distinct clusters occurring in December 2016, and in October 2019. The October 2019 earthquake swarm, the best recorded sequence in the area, provides evidence for the underlying triggering mechanism. We show that a complex mechanism that includes fluid migration and aseismic processes is responsible for the earthquake swarm evolution. We hypothesize that these episodic swarms in the Mineral Mountains are primarily driven by migrating fluids that originate within the Roosevelt hydrothermal system Key Points: We find 1, 100 earthquakes in the Mineral Mountains, Utah during 2016–2019 using a matched‐filter method and 75 earthquake templates Fluctuations of the seismicity rate with periods of burst‐like activity followed by quiescence shows 15 swarm‐like sequences Spatial and temporal evolution of burst‐like seismicity is related to fluid diffusion with possible episodes of aseismic slip